THE CORRELATION BETWEEN GALECTIN-3, CREATININE AND URIC ACID ON STAGE V CHRONIC RENAL FAILURE - Indranila K S; Guruh A I; Meita H (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Chronic Renal Failure (CRF) is structural damage and function of the kidneys that cannot excrete toxins and waste products from the blood, characterized by the presence of protein in the urine and decreased glomerulus filtration rate. This study aimed to determine the correlation between Galectin-3 and markers of kidney function which are creatinine and uric acid. This study was being concluded on 33 CRF patients who were doing hemodialysis therapy. This study was conducted in the Dr. Kariadi Semarang Hospital and GAKI Laboratory of Diponegoro Medical Faculty from April to June 2018. The research method was analytical descriptive with cross-sectional approach. Galectin-3 was analyzed using ELISA method with an automatic analyzer, creatinine and uric acid using the colorimetric method with an automatic spectrophotometer. Statistical analysis used Shaphiro-Wilk normality test and Spearman correlation test. There is a weak positive correlation test of galectin-3 with creatinine (r = 0.381; p = 0.029) and galectin-3 with uric acid (r = 0.374; p = 0.048) in CRF – HD. It is concluded galectin-3 can be used as a marker of kidney function.